Punching Shear in Post-Tensioned Flat Slabs with Shear Reinforcement: Codes and Tests - Carvalho, Alessandra L.; Melo, Guilherme S.; Gomes, Ronaldo B. (ACI structural journal, 2016)
The experimental punching capacities results of 27 punching tests on 160 to 200 mm (6.30 to 7.87 in.) deep post-tensioned slabs-all but three of them containing stud-rail shear reinforcement-are compared with resistances calculated by the methods of ACI 318 and Eurocode 2. The experimental study describing 17 of these tests were published in a previous paper. The slabs, 200 mm (7.87 in.) thick and 3.0 m (9.84 ft) square, were loaded at their centers and simply supported near their edges. Fifteen contained shear reinforcement in the form of stud rails and the principal variables in the series were those of the shear reinforcement. The study concluded that both codes' equations are conservative and suggestions on amendments are presented to improve their accuracies, based on experimental results.